Observed meltwater-induced flexure and fracture at a doline on George VI Ice Shelf, Antarctica - Alison F. Banwell; Ian C. Willis; Laura A. Stevens; Rebecca L. Dell; Douglas R. MacAyeal (Journal of Glaciology)
Global Navigation Satellite System (GNSS) observations and ground-based timelapse photography obtained over the record-high 2019/2020 melt season are combined to characterise the flexure and fracture behaviour of a previously formed doline on George VI Ice Shelf, Antarctica. The GNSS timeseries shows a downward vertical displacement of the doline centre with respect to the doline rim of ~60 cm in response to loading from a central meltwater lake. The GNSS data also show a tens-of-days episode of rapid-onset, exponentially decaying horizontal displacement, where the horizontal distance between the doline rim and its centre increases by ~70 cm. We interpret this event as the initiation and/or widening of a fracture, aided by stress perturbations associated with meltwater loading in the doline basin. Viscous flexure modelling indicates that the meltwater loading generates tensile surface stresses exceeding 75 kPa. This, together with our timelapse photos of circular fractures around the doline, suggests the first such documentation of meltwater-loading-induced ‘ring fracture’ formation on an ice shelf, equivalent to the fracture type proposed as part of the chain-reaction lake drainage process involved in the 2002 breakup of the Larsen B Ice Shelf.